2014
DOI: 10.1016/j.ijmm.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Polyketide synthase (PKS) reduces fusion of Legionella pneumophila-containing vacuoles with lysosomes and contributes to bacterial competitiveness during infection

Abstract: CitationPolyketide synthase (PKS) reduces fusion of Legionella pneumophila-containing vacuoles with lysosomes and contributes to bacterial competitiveness during infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…1) while one other PKS derived compound has been implicated in lysosomal degradation (Shevchuk et al, 2014). Legioliulin is a trans -AT PKS derived fluorophore (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) while one other PKS derived compound has been implicated in lysosomal degradation (Shevchuk et al, 2014). Legioliulin is a trans -AT PKS derived fluorophore (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…From Legionella , only four BGCs have been explored in detail with three secondary metabolites structurally elucidated to date (Fig. 1) (Ahrendt et al, 2013; Shevchuk et al, 2014; Burnside et al, 2015; Johnston et al, 2016a). Legioliulin (1), a product of a trans -AT PKS cluster first identified in L. dumoffii, was reported originally in 2004 (Amemura-Maekawa et al, 2004) and biological activity assays failed to determine a role for the compound beyond fluorescence (Ahrendt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major outer membrane protein (MOMP) of L. pneumophila binds complement component C3 and C3i and mediates the uptake of the bacteria via the complement receptors CR1 and CR3 of macrophages. Phagocytosed L. pneumophila recruit compartments from the endoplasmatic reticulum (ER), modulate the host phosphoinositide metabolism, modify the host endocytic pathway, intercept vesicle trafficking and avoid fusion with lysosomes (Shevchuk et al, 2014). The development of the Legionella -containing vacuole (LCV) is pre-dominantly orchestrated by the Dot/Icm type IV secretion system, which is known to export numerous bacterial effector proteins into the host cell cytoplasm (Horwitz, 1983; Kagan and Roy, 2002; Isberg et al, 2009; Hubber and Roy, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we screened a L. pneumophila mini-Tn10 transposon library for mutants that fail to avoid fusion of their respective LCV with lysosomes (Shevchuk et al, 2014). The range of the identified mutants indicated that interference with lysosomal degradation is multifactorial.…”
Section: Introductionmentioning
confidence: 99%